2006
DOI: 10.1093/pubmed/fdl045
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to kidney donation and registering as a donor among ethnic groups in the UK

Abstract: Low rates of registration as a kidney donor among ethnic minorities are not explained by specific cultural or religious barriers. More adequate explanations require a broader focus and greater understanding of ways in which self-identity as a minority group, cultural and religious beliefs and practices, and the social capital of communities, interact to shape responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 15 publications
2
71
0
Order By: Relevance
“…Similar anxieties have been expressed in other ethnic minority populations including Chinese-Canadians; 31 Hispanics, African-Americans and Asian-Americans in the USA; [32][33][34][35] and black Caribbean and black Africans in the UK. 5 While these beliefs may be easily dismissed as misconceptions in the Western context, our study provides new insights as members of the Arabic-speaking community explained their origin of beliefs to be based on publicised healthcare practices reportedly occurring in the Middle East, for example, black market trading of organs, bribery for organs and removal of organs before being declared deceased.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Similar anxieties have been expressed in other ethnic minority populations including Chinese-Canadians; 31 Hispanics, African-Americans and Asian-Americans in the USA; [32][33][34][35] and black Caribbean and black Africans in the UK. 5 While these beliefs may be easily dismissed as misconceptions in the Western context, our study provides new insights as members of the Arabic-speaking community explained their origin of beliefs to be based on publicised healthcare practices reportedly occurring in the Middle East, for example, black market trading of organs, bribery for organs and removal of organs before being declared deceased.…”
Section: Discussionmentioning
confidence: 80%
“…This is reflected in their limited proportion of organ donor registrations and family consent when organ donation is discussed in the acute hospital setting. [5][6][7][8][9] In the USA, the deceased organ donation consent rate between 2008 and 2011 for the white population was 77.0%, compared with 67.5% for Hispanics, 54.9% for African-Americans and 48.1% for Asians. 6 Similar trends have also been noted in the UK where ethnic minority groups account for 8% of the population, but constitute 24% of the waiting list for kidneys, 10 and only 3% of deceased donors.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have shown that cultural issues are important influencing factors when making a decision about organ donation [1,2] although the influence of belief and faith systems is less clear [3][4][5][6][7][8]. There are significant disparities between ethnic groups which are reflected in the organ waiting lists.…”
Section: Introductionmentioning
confidence: 99%
“…This might suggest that in signing a donor card or agreeing to donate a relative's organs, South Asians will be particularly influenced by appeals focussing on the needs of their own community. Studies in both the USA and UK have indicated that minority members may be unwilling to contribute to "the general good", since they feel marginalised from mainstream society through economic disadvantage and/or through the experience of racism (Morgan and Cannon 2003;Morgan et al 2006). Illness and the topic of death itself may bring issues of cultural identity to the fore (Morgan et al 2008).…”
Section: Discussionmentioning
confidence: 99%